Deformation and failure characteristics of high-speed tunnels in complex karst areas: a case at the Qilinguan tunnel - Hu, Changgeng (Frontiers in Earth Science, 2023)
The construction of expressway tunnels in karst areas faces many challenges under complex geological conditions. It is of great scientific and engineering significance to study the deformation and failure law of tunnels and surface. Taking the Qilinguan tunnel of Hubei expressway as an example, the deformation and failure law of the tunnel is analyzed, when the tunnel passes through the complex karst area. The composition of karst water and surrounding rock were analyzed by inductively coupled plasma mass spectrometry and XRD, and the compression-shear failure model of tunnel in karst area was proposed according to the regional hydrological and geological conditions. It was found that the thickness of protective layer and the water pressure were the main factors affecting the deformation and failure of surrounding rock in this area, and the treatment scheme of this project was put forward accordingly. The geological characteristics of karst area are explored by advanced geological prediction and advanced geological drilling. The primary support is carried out by steel arch and advanced small pipe grouting. The composite lining is composed of shotcrete primary support and molded concrete secondary lining. The primary support structure of flexible support system is adopted in the design to give full play to the bearing capacity of surrounding rock. After the support measures are adopted, the trend of settlement change gradually slowed down, indicating that the support measures were effective.